Genetic Profiling by Single‐Nucleotide Polymorphism‐Based Array Analysis Defines Three Distinct Subtypes of Orbital Meningioma. (21st May 2014) - Ho, Cheng‐Ying; Mosier, Stacy; Safneck, Janice; Salomao, Diva R.; Miller, Neil R.; Eberhart, Charles G.; Gocke, Christopher D.; Batista, Denise A. S.; Rodriguez, Fausto J.
Abstract Orbital meningiomas can be classified as primary optic nerve sheath (ON) meningiomas, primary intraorbital ectopic (Ob) meningiomas and spheno‐orbital (Sph‐Ob) meningiomas based on anatomic site. Single‐nucleotide polymorphism (SNP)‐based array analysis with the Illumina 300K platform was performed on formalin‐fixed, paraffin‐embedded tissue from 19 orbital meningiomas (5 ON, 4 Ob and 10 Sph‐Ob meningiomas). Tumors were World Health Organization (WHO) grade I except for two grade II meningiomas, and one was NF2‐associated. We found genomic alterations in 68% (13 of 19) of orbital meningiomas. Sph‐Ob tumors frequently exhibited monosomy 22/22q loss (70%; 7/10) and deletion of chromosome 1p, 6q and 19p (50% each; 5/10). Among genetic alterations, loss of chromosome 1p and 6q were more frequent in clinically progressive tumors. Chromosome 22q loss also was detected in the majority of Ob meningiomas (75%; 3/4) but was infrequent in ON meningiomas (20%; 1/5). In general, Ob tumors had fewer chromosome alterations than Sph‐Ob and ON tumors. Unlike Sph‐Ob meningiomas, most of the Ob and ON meningiomas did not progress even after incomplete excision, although follow‐up was limited in some cases. Our study suggests that ON, Ob and Sph‐Ob meningiomas are three molecularly distinct entities. Our results also suggest that molecular subclassification may have prognostic implications.